2001
DOI: 10.1093/humrep/16.10.2084
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of sperm chromosomal abnormalities in a risk population: relationship with sperm quality and ICSI outcome

Abstract: Patients with a clinical background of recurrent miscarriages of unknown aetiology or implantation failure after ICSI are at risk of showing sperm chromosomal abnormalities, the incidence of which is higher in oligoasthenoteratozoospermic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
89
1
6

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(103 citation statements)
references
References 33 publications
7
89
1
6
Order By: Relevance
“…Since the use of testicular spermatozoa in ICSI programs leads to a lower ongoing pregnancy and delivery rates as a result of a higher abortion rate compared to epididymal or ejaculated spermatozoa, 12,23 it can be hypothesised that this is an effect of a higher number of aneuploid spermatozoa found in these patients. 24 The finding that also patients with OA have an increased sperm aneuploidy rate compared to controls suggests that a certain degree of spermatogenetic impairment exists also in these patients. 25 In conclusion, this study has shown that spermatozoa retrieved from the epididymes or the testes of patients with azoospermia have an increased aneuploidy rate.…”
Section: Discussionmentioning
confidence: 99%
“…Since the use of testicular spermatozoa in ICSI programs leads to a lower ongoing pregnancy and delivery rates as a result of a higher abortion rate compared to epididymal or ejaculated spermatozoa, 12,23 it can be hypothesised that this is an effect of a higher number of aneuploid spermatozoa found in these patients. 24 The finding that also patients with OA have an increased sperm aneuploidy rate compared to controls suggests that a certain degree of spermatogenetic impairment exists also in these patients. 25 In conclusion, this study has shown that spermatozoa retrieved from the epididymes or the testes of patients with azoospermia have an increased aneuploidy rate.…”
Section: Discussionmentioning
confidence: 99%
“…Although errors of nondisjunction occur to a lesser extent in sperm than in oocytes, paternal errors are responsible for the majority of cases of the sex chromosome trisomies XXY and XYY (Chamley et al 1993;Hawley et al 1994 (Rubio et al 2001). A 2003 case control study that examined the presence of sperm chromosomal aneuploidy and apoptosis in couples with unexplained RPL also showed a significantly increased mean aneuploidy rate in this group compared with the control groups (Carrell et al 2003).…”
Section: Fetal Aneuploidy In Sporadic and Recurrent Pregnancy Lossmentioning
confidence: 91%
“…The study cited for a support of this statement, however, never investigated men with sperm aneuploidy, but rather looked at all couples with recurrent pregnancy loss due to any number of reasons [17]. The other paper cited in the ASRM 2012 statement, in fact, contradicts their statement by demonstrating that couples with abnormal sperm FISH results showed decreased pregnancy and implantation rates and increased miscarriage rates [8]. Thus, until more in-depth studies can be performed to explore this relationship between sperm aneuploidy and pregnancy outcomes, men with recurrent pregnancy loss should be screened for sperm aneuploidy.…”
Section: Recurrent Pregnancy Lossmentioning
confidence: 99%
“…Recurrent pregnancy loss (RPL), which may be defined as two or more pregnancy losses less than 20 weeks after the last menstrual period, is experienced by 1 to 2 % of women [2,3]. While there are many genetic causes for male factor infertility, for couples who have experienced RPL or repeated in vitro fertilization (IVF) failures, male chromosomal aneuploidy or chromosomal structural aberrations (such as translocation, inversion, and pericentric inversion) are of particular concern [4][5][6][7][8]. Aneuploidy is defined as an abnormal number of chromosomes (too few or too many) in a cell due to abnormal meiosis.…”
Section: Introductionmentioning
confidence: 99%